Teaching knowledge in times of rising neo-conservatism: how teachers approach gender and sexuality in Science classes (Research, Society and Development, 2020)
We know that, even with the emergence of neoconservative movements that go against the approach of gender relations and sexuality at school, there are teachers who resist this backward wave and work with a theme. We sought three science teachers who already addressed these topics in class, through a social network. An individual and face-to-face interview, with a script of questions, was recorded, audio recorded and transcribed. Our objective was to answer how the science teachers interviewed approach the theme of gender and sexuality relations in the classroom. We conducted a qualitative research, more precisely a case study. The analyzes of this study, using the Discursive Textual Analysis method, indicated that the teachers seek to relate the science content to gender, sexuality and the students' social context. We realized that there is no way to silence debates on the topic, since many of the questions come from the curiosity of the students themselves. We understand, therefore, that it is necessary to work on science content that includes a perspective of respect for diversity and the fight against inequalities and that are allied to the interests of students. We also emphasize that, according to the subjects of this research, the family, the school and the teachers themselves can express resistance to the debates. We also realized that the lack of information from teachers about gender and sexuality can be an obstacle to the realization of teaching practices on the themes. Therefore, the need for continuing education courses in gender and diversity and support materials related to the themes is highlighted.